A review of drag reduction by additives in curved pipes for single‐phase liquid and two‐phase flows. Issue 3 (27th October 2020) - Ayegba, Paul O.; Edomwonyi‐Otu, Lawrence C.; Yusuf, Nurudeen; Abubakar, Abdulkareem
Abstract: The effect of drag‐reducing agents (DRAs) on fluid flows in straight pipes has been well documented. Key among these is the effect of DRAs on turbulence statistics (Reynolds shear stress, turbulence intensity, streamwise and wall‐normal velocity fluctuation among others). These primary effects result in secondary effects such as modification of mean velocity profile and reduction in frictional losses (drag reduction, DR). Interestingly, in curved pipe flows, the characteristic of flow is more complex due to secondary flow, wake effects and under‐developed flow characteristics. Therefore, a review of investigations on the effect of DRAs in curved pipe flows is presented in this paper. The paper highlights the difference between DR in straight and curved conduits as well as the interaction between DRAs and flow characteristics of curved pipe flows. Proposed mechanisms of DR, and factors that influence their effectiveness also received attention. It was shown that significant DR can be achieved in curved pipes. A review of various experimental results revealed that DR by additives in curved pipes is generally lower than in straight pipes but with certain similarities. It decreases with increase in curvature ratio and is more pronounced in the transition and turbulent flow regimes. Maximum DR asymptote differed between straight and curved pipes and between polymer and surfactant. Due to the limited studies in the area of DR for gas‐liquid flow in curved pipes, no definite conclusion could be drawn on the effect of DRAs on such flows. A number of questions remain such as physical interaction between molecules of DRA and flow features such as secondary flow streamlines and wakes. Hence, some research gaps have been identified with recommendations for areas of future researches. Abstract : A review of investigations on the effect of drag‐reducing agents in flows around curved pipes and bends is presented. Drag reduction in curved pipe flows are generally lower than in straight pipes and the mechanism is still not generally accepted. This review is a launch pad for future research as it highlighted some research gaps with appropriate recommendations.